IDEOLOGIZATION OF MBRAKAH IN MAINTAINING INDONESIA SUSTAINABLE FOOD SYSTEM: Extracting From Pesantren’s Values and Prophetic Tradition - Rizqa Ahmadi; Wildani Hefni (AL-TAHRIR, 2023)
Originally, mbrakah was a practice of food combining or food custom for spiritual purposes. The mbrakah tradition also can be categorized as 'food fashion.' In the global academic discourse, food culture and spirituality are important issues with strong traditional roots in Sufism and prophetic traditions, especially in Sufism. Particularly, mbrakah is even more unique because it is rooted in Sufism traditions and early Islamic norms and has been in dialogue with local wisdom, namely Indonesian Culture and, more specifically, Pesantren culture. One of the oldest Islamic educational institutions in Indonesia. In this article, We conceptualize that the mbrakah tradition does not merely stop as a food-combining tradition only carried out for personal interests. Based on the literature review, we argue that mbrakah can be transformed from theology to food ideology. Although the ideology referred to in the article is not an ideology in a complex sense, it can be a way of thinking and manifested into a movement and shared awareness about the importance of successful food diversification for food security during food problems in Indonesia. Mbrakah is a local culture and holds a religious dimension that many researchers consider, and it has the potential to be highly effective as a transformative movement.